P069: Does specialist referral influence emergency department return rate for patients with renal colic? A retrospective cohort study. (May 2019) - Kanji, A.; Atkinson, P.; Massaro, P.; Pawsey, R.; Whelan, T.
Abstract : Introduction : Renal colic is a common presentation which exerts a significant burden on healthcare infrastructure. A significant proportion of patients managed with observation may return to the Emergency Department (ED) prior to spontaneous passage due to inadequate analgesia. It is unclear whether early urologist consultation would limit the burden of renal stones by reducing returns to the ED. We wished to determine whether urologist referral from the ED department is associated with fewer returns to the ED with renal colic.Methods : We conducted a retrospective chart review using RECORD methodology of consecutive patients diagnosed with CT-confirmed, ureteric or renal calculi in our ED over a two-year period. Disposition was categorized as either hospital admission, outpatient urologist referral, follow up with primary care, or no follow up. The primary outcome was the 30-day ED re-presentation for renal colic. Multivariate logistic regression was used to identify predictors for ED-return.Results : In total, 232 patients met our inclusion criteria. Urgent or outpatient urologist referral was not associated with a significantly lower ED return rate when compared to patients with no follow-up. Surprisingly, urologic intervention and stent placement were both independent predictors for ED return (OR: 2.03; 95% CI: (1.06-3.88); p:0.03) and (OR:2.08; 95% CI: (1.07-4.05).Conclusion : A significant proportion of patients who underwent urologist-led intervention returned to the ED with renal colic. Further study may help clarify the role of early urologist referral for renal calculi, as this may not reduce ED return rates when compared to conservative management.